Efforts to Improve Legal Compliance Through the Writing of the Awig Screening Pararems in the Dalem Yangapi Traditional Village - I Ketut Sukadana; Ni Made Jaya Senastri; I Made Gianyar; Kadek Ayu Surya Dwi Utami; Ni Putu Putri Pebriyanti Apsari (Community Service Journal of Law, 2025)
One factor for good law enforcement is legal awareness and compliance with the law. Legal compliance can be achieved through the existence of good regulations. In Bali, Customary Villages (Desa Adat) are traditional villages in Bali that have autonomy in creating regulations. Each Customary Village has its own administrators and assets, and has the authority to create regulations, known as awig-awig and/or pararem. The situation of the program partners is that they do not yet have a pararem panyahcah awig as a regulation for implementing awig-awig. The goal of this program is to empower the Customary Village community so that they have a regulation in the form of a pararem panyahcah awig. The methods used in this community service program are: (1) providing lectures or legal counseling on the importance of a pararem panyahcah awig in life in a Customary Village, (2) conducting focus group discussions (FGDs) on the draft pararem, and (3) providing assistance in creating customary village pararem. The result of this program is the development of a set of 64 articles (pawos) to address customary law (adat), in accordance with the mandate of the customary law (adat) outlined in the articles.